Penggunaan Sarana Prasarana dalam Mendukung Mutu Pembelajaran di SMKS 6 Pertiwi Curup - Sandiya Desti Ayunisyah; Sutarto Sutarto; Baryanto Baryanto (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research aims to determine the use of facilities and infrastructure to support the quality of learning. This type of research is qualitative with a descriptive approach. Data sources were obtained from observations of the school environment, interviews with the principal and head of infrastructure, and documentation. The collection techniques in this research are observation, discussion, and documentation. Data analysis techniques are reduction, display, conclusion drawing and verification, and descriptive statistics. The results of this research show that the use of infrastructure to support the quality of learning at SMKS 6 Pertiwi Curup is carried out in stages, namely, preparing different usage schedules, making learning activities a priority, submitting a usage schedule at the beginning of the school year, assigning/appointing personnel, and scheduling the use of facilities. Infrastructure for intracurricular and extracurricular activities. In conclusion, the use of facilities and infrastructure to support the quality of learning at SMKS 6 Pertiwi Curup is preparing schedules so that there are no conflicts between classes and submitting programs at the beginning of the school year, using infrastructure specifically for learning activities which are the main priority, as well as scheduling extracurricular and extracurricular activities clear. Keywords: Infrastructure, Use, Learning Quality